IMPLEMENTASI PENYELENGGARAAN E-GOVERNMENT (Studi Kasus Peraturan Bupati Tabalong Nomor 09 Tahun 2017) - Eddy Suriyani (Jurnal PubBis, 2018)
Research objectives are 1) Knowing the construction of infrastructure and facilities in the District E-Government Tabalong. 2) Identify factors driving and inhibiting the development of E-Government policy in the District Tabalong. 3) Find a solution that has been done to address the factors inhibiting the implementation of E-Government in the District Tabalong. The research conducted was descriptive method. The population in this study is the District Government Bureaucrats officials as many as 6 people Tabalong technique of determining the sample was purposive sampling. Interview data collection techniques and documentation. While the processing techniques and data analysis using qualitative descriptive techniques. From the results showed that: 1) Development of infrastructure and E-Government in the District Tabalong not fully come to fruition. 2) Inhibiting factor found in the development of E-Government in the District Tabalong consist of such factors as: a) the individual cultural barriers, b) Development of systems / applications lack of planning and coordination among SKPD so it is not uncommon to have purchased an application that can not be utilized optimally, c) The budget is still minimal and the absence of contract after installation of information systems developers and there is no agency that specifically examines the development of standards or specifications and the development of E-Government system by default. 3) The solution in implementing e-Government policy on Tabalong district is to provide computer networking facilities and adequate in every SKPD and support the data is accurate and up to date periodically and is accessible to all parties who need to use ICT and qualified human resources to support decision-making process environment Tabalong County Government, harmonious cooperation with all relevant SKPD on the development of systems / ICT-based applications according to existing regulations, to allocate a special budget for the development of e-government as well as the formulation of Standard Operating Procedure (SOP) is clear and supported The team with the formation or function taks force that runs the E-Government implementation environment Tabalong Regency Government. Keywords: implementation; policy; E-government; ICT